2023
DOI: 10.1002/cac2.12480
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral CD103+CD8+ T cells predict response to neoadjuvant chemoimmunotherapy in advanced head and neck squamous cell carcinoma

Siqi Ren,
Tianjun Lan,
Fan Wu
et al.

Abstract: BackgroundImmune cell heterogenicity is known to determine the therapeutic response to cancer progression. Neoadjuvant chemoimmunotherapy (NACI) has shown clinical benefits in some patients with advanced head and neck squamous cell carcinoma (HNSCC), but the underlying mechanism behind this clinical response is unknown. The efficacy of NACI needs to be potentiated by identifying accurate biomarkers to predict clinical responses. Here, we attempted to identify molecules predicting NACI response in advanced HNSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In addition, the authors demonstrated that fecal microbiota transplantation (FMT) from feces of responder patients into mice, restored NACI antitumor activity ( 18 ). The efficacy of NACI treatment is positively correlated to a high concentration of intratumoral CD103 + CD8 + in head and neck squamous cell carcinoma (HNSCC) patients, as observed by Ren et al ( 19 ).…”
mentioning
confidence: 74%
“…In addition, the authors demonstrated that fecal microbiota transplantation (FMT) from feces of responder patients into mice, restored NACI antitumor activity ( 18 ). The efficacy of NACI treatment is positively correlated to a high concentration of intratumoral CD103 + CD8 + in head and neck squamous cell carcinoma (HNSCC) patients, as observed by Ren et al ( 19 ).…”
mentioning
confidence: 74%